Cytomegalovirus retinitis and telemedicine - Ausayakhun, Sakarin; Ausayakhun, Somsanguan (Biomedical Sciences and Clinical Medicine, 2024)
The most common ocular opportunistic infection in AIDS patients is cytomegalovirus (CMV) retinitis, which is characterized by dense retinal whitening and hemorrhage. An experienced ophthalmologist can detect CMV retinitis by looking through a dilated pupil in a highly sensitive and specific manner. This indirect ophthalmoscopy technique does not need expensive equipment, but it does require a high level of expertise and time consumption from ophthalmologists. However, telemedicine can enhance the ability of general practitioners in providing CMV retinitis care, and it is possibly the most reliable method for improving screening of this blinding disease. Telemedicine could be used in the future for screening CMV retinitis, and providing a forum for both monitoring quality control and mentoring trainee non- ophthalmologists.